A Meta-analytic Study on Executive Function Performance in Children/Adolescents with OCD - López-Hernández, Paloma; Sánchez-Meca, Julio; Rosa-Alcázar, Ángel; Rosa-Alcázar, Ana Isabel (Anales de Psicología / Annals of Psychology, 2022)
Background: The main objective of this work was to carry out a meta-analytical study to examine performance in executive functions in children/adolescents with obsessive-compulsive disorder (OCD). Method: A comprehensive literature search from 1984 to September 2021 was conducted, selecting a total of 20 published studies comparing executive function outcomes among a group of children and/or adolescents with OCD and a healthy control group. Results: Results showed that the total score on the quality scale of studies ranged between 3 and 8.5 points (on a scale of 0 to 9), with a mean of 6.6. The effect sizes in the different executive functions were as follows: Inhibition (d+ = -0.221), Cognitive flexibility (d+ = -0.418), Decision making (d+ = -0.169) and Planning (d+ = -0.319), indicating a lower performance in the OCD groups compared to the healthy control groups. Results were clinically significant in all domains except decision making. Publication bias could only be carried out in flexibility and response inhibition. Conclusions: OCD patients presented worse executive performance than healthy controls in all functions, highlighting cognitive flexibility and planning. However, results should be interpreted with caution due to the small sample size.